AN ELASTIC-PLASTIC MICROCONTACT MODEL OF ASPERITIES - Jamari, Jamari (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2006)
In this paper a theoretical model for the elastic-plastic microcontact model of asperities is presemted. Relationof the contact parameters, such as the mean contact pressure, the contact area and the contact load as a function of thecontact interference are modeled in the elastic, elastic-plastic and fully plastic contact regime. The model is verified bythe experimental results and is compared with published theoretical models. Very good agreement between the presentmodel and the experimental results are found compared to the prediction of the other contact models.